The potential benefits and drawbacks of a cashless society (Journal of Science-Innovative Research in Uzbekistan, 2024)
The transition to a cashless society, characterized by the replacement of physical currency with digital transactions, has garnered significant attention in recent years. This paper explores the multifaceted implications of such a shift, weighing its potential benefits and drawbacks. Key advantages include increased convenience and efficiency in transactions, enhanced security through reduced risk of theft and counterfeiting, and improved financial inclusion for those with access to digital technology. Additionally, cashless transactions can provide better tracking and transparency, aiding in the reduction of tax evasion and illicit activities.Conversely, the drawbacks encompass concerns over privacy and data security, the risk of digital fraud, and the exclusion of individuals lacking access to digital infrastructure. Furthermore, the dependence on technology raises the vulnerability to cyberattacks and system failures. This analysis underscores the need for balanced policy approaches that maximize the benefits while mitigating the risks associated with a cashless society